Systematic Review of AppSheet-Based Attendance Systems: Outcomes, Features, and Sectoral Adoption - Muh Dliyaul Haq; Nova Tri Prasetiyo; Aris Setianto (Universitas Dian Nuswantoro, 2025)
The digitalization of organizational processes has accelerated the adoption of efficient attendance management systems. This study systematically reviews AppSheet-based digital attendance implementations, focusing on outcomes, features, and sectoral adoption. Following a PRISMA-guided systematic literature review, 23 studies published between 2020 and 2025 were analyzed. Findings indicate that AppSheet enhances efficiency, accuracy, transparency, and user satisfaction, primarily through mobile access, GPS-based geolocation, QR code verification, and cloud-based reporting. Selfie photo with GPS emerged as the most common feature, followed by QR code–based attendance, while additional functionalities such as digital signatures and form-based attendance provide complementary solutions. Adoption is concentrated in the education sector, particularly primary and secondary schools, with limited uptake in government and corporate contexts. Challenges include scalability limits in free versions, proxy attendance risks, internet dependency, and storage constraints. The study underscores AppSheet’s flexibility as a no-code platform, offering practical, cost-effective, and adaptive solutions for digital attendance management across diverse organizational settings.